login
This site is supported by donations to The OEIS Foundation.

 

Logo

Annual Appeal: Please make a donation (tax deductible in USA) to keep the OEIS running. Over 5000 articles have referenced us, often saying "we discovered this result with the help of the OEIS".

Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A157181 A new general triangle sequence based on the Eulerian form in three parts ( subtraction):m=3; t0(n,k)=If[n*k == 0, 1, Sum[(-1)^j Binomial[n + 1, j](k + 1 - j)^n, {j, 0, k + 1}]] t(n,k,m)=If[n == 0, 1, ( m*(n - k) + 1)*t0(n - 1 + 1, k - 1) + (m*k + 1)*t0(n - 1 + 1, k) - m*k*(n - k)*t0(n - 2 + 1, k - 1)]. 0

%I

%S 1,1,1,1,5,1,1,17,17,1,1,45,106,45,1,1,105,524,524,105,1,1,229,2231,

%T 4258,2231,229,1,1,481,8547,28771,28771,8547,481,1,1,989,30424,171283,

%U 290126,171283,30424,989,1,1,2009,102926,928070,2505074,2505074,928070

%N A new general triangle sequence based on the Eulerian form in three parts ( subtraction):m=3; t0(n,k)=If[n*k == 0, 1, Sum[(-1)^j Binomial[n + 1, j](k + 1 - j)^n, {j, 0, k + 1}]] t(n,k,m)=If[n == 0, 1, ( m*(n - k) + 1)*t0(n - 1 + 1, k - 1) + (m*k + 1)*t0(n - 1 + 1, k) - m*k*(n - k)*t0(n - 2 + 1, k - 1)].

%C Row sums are:

%C {1, 2, 7, 36, 198, 1260, 9180, 75600, 695520, 7076160, 78926400,...}.

%C The m=0 of the general sequence is A008518.

%F m=3;

%F t0(n,k)=If[n*k == 0, 1, Sum[(-1)^j Binomial[n + 1, j](k + 1 - j)^n, {j, 0, k + 1}]];

%F t(n,k,m)=If[n == 0, 1, ( m*(n - k) + 1)*t0(n - 1 + 1, k - 1) +

%F (m*k + 1)*t0(n - 1 + 1, k) +

%F m*k*(n - k)*t0(n - 2 + 1, k - 1)].

%e {1},

%e {1, 1},

%e {1, 5, 1},

%e {1, 17, 17, 1},

%e {1, 45, 106, 45, 1},

%e {1, 105, 524, 524, 105, 1},

%e {1, 229, 2231, 4258, 2231, 229, 1},

%e {1, 481, 8547, 28771, 28771, 8547, 481, 1},

%e {1, 989, 30424, 171283, 290126, 171283, 30424, 989, 1},

%e {1, 2009, 102926, 928070, 2505074, 2505074, 928070, 102926, 2009, 1},

%e {1, 4053, 336109, 4684096, 19330402, 30217078, 19330402, 4684096, 336109, 4053, 1}

%t Clear[t, n, k, m];

%t t[n_, k_, m_] = (m*(n - k) + 1)*Binomial[n - 1, k - 1] + (m*k + 1)*Binomial[n - 1, k] - m*k*(n - k)*Binomial[n - 2, k - 1];

%t Table[t[n, k, m], {m, 0, 10}, {n, 0, 10}, {k, 0, n}];

%t Table[Flatten[Table[Table[t[n, k, m], {k, 0, n}], {n, 0, 10}]], {m, 0, 10}]

%t Table[Table[Sum[t[n, k, m], {k, 0, n}], {n, 0, 10}], {m, 0, 10}];

%Y A008518

%K nonn,tabl

%O 0,5

%A _Roger L. Bagula_ and _Gary W. Adamson_, Feb 24 2009

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent | More pages
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy .

Last modified December 5 11:38 EST 2016. Contains 278764 sequences.